Gamification in the Teaching-Learning Process of Social Studies to Encourage Participation in Basic General Education - Yanes, Lady Elizabeth Castillo; Camacho, Sor Natalia Brizuela (Journal of Ecohumanism, 2024)
Currently, the development of new information technologies has generated great changes, including in its advancement to the educational sector, hence this research addresses gamification in the teaching-learning process of Social Studies to encourage participation in general education. basic; The population is limited to a sample of 31 students, corresponding to the 10th year of basic general education of the “Miguel Ángel Suárez” high school in the city of Loja, the methodological approach used is quantitative, and is combined with quantitative descriptive research to gain a complete and accurate understanding of the effects of gamification on student engagement. A questionnaire was used to evaluate the perception and participation of the students. The results obtained highlight the need to adapt active methodologies to satisfy the demands of today’s society and promote digital skills in the classroom. This research highlights the importance of transforming traditional education towards more engaging and participatory approaches, where gamification can play a fundamental role in improving the educational process and student engagement.